2018
DOI: 10.21511/ppm.16(3).2018.30
|View full text |Cite
|
Sign up to set email alerts
|

South Africa University students’ perceptions of key education service quality determinants

Abstract: Understanding higher education (HE) service quality is critical for success in a highly competitive environment, since through a better understanding of the determinants of HE service quality, HE managers and leaders could better manage HE service quality better. A survey was conducted among a purposive judgmental sample of 400 students, from two HE institution campuses in SA, to identify their perceptions of key service quality determinants (KSQDs), and the importance of the KSQDs, by using a semi-structured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…If government support to public universities is dwindling at a time when these public institutions are also competing with private universities in the supply of university education, quality becomes a critical issue that 'buyers' (students) consider to decide where to enroll and access tertiary education. A study of this kind, therefore, becomes crucial since it provides an opportunity to ascertain students' perceptions of quality service delivery (Sanjay & Govender, 2018). Based on the perceptions, the universities could put in place quality assurance mechanisms to address some of their challenges that often fuel the negative perceptions among students, and which usually tend to be inimical to the image of public universities.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…If government support to public universities is dwindling at a time when these public institutions are also competing with private universities in the supply of university education, quality becomes a critical issue that 'buyers' (students) consider to decide where to enroll and access tertiary education. A study of this kind, therefore, becomes crucial since it provides an opportunity to ascertain students' perceptions of quality service delivery (Sanjay & Govender, 2018). Based on the perceptions, the universities could put in place quality assurance mechanisms to address some of their challenges that often fuel the negative perceptions among students, and which usually tend to be inimical to the image of public universities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Good quality education is the one that provides all learners with the capabilities they require to become economically productive, develop sustainable livelihoods, contribute to peaceful and democratic societies, and enhance individual well-being (Mwanga, 2015). Recent studies identified the dimensions of quality higher education as quality of students, faculty credentials, academic features, and administrative supports (Akareem & Hossain, 2012;Sanjay & Govender, 2018). Schargel (1996) stated that modern universities are experiencing a 'buyers' market' and that students are buying higher education from universities via the curriculum, faculties, library, resources offered, and more importantly SSR analyses among others (Wallisch & Cachia, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation